2020
DOI: 10.1186/s40164-020-00194-y
|View full text |Cite
|
Sign up to set email alerts
|

Applications of gut microbiota in patients with hematopoietic stem-cell transplantation

Abstract: Studies of the gut microbiota (GM) have demonstrated the close link between human wellness and intestinal commensal bacteria, which mediate development of the host immune system. The dysbiosis, a disruption of the microbiome natural balance, can cause serious health problems. Patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT) may cause significant changes in GM due to their underlying malignancies and exposure to extensive chemotherapy and systemic antibiotics, which may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 108 publications
0
8
0
1
Order By: Relevance
“…The influence of gut microbiota on host immunity is multifaceted, simultaneously regulating the gut mucosal immune system and systemic immune system (Fig. 2d) [307][308][309][310]. It was reported that the gut microbiota of immunotherapy-sensitive patients was distinct from that of immunotherapy-resistant populations [311,312].…”
Section: Fmt Plus α-Pd-1/pd-l1mentioning
confidence: 99%
“…The influence of gut microbiota on host immunity is multifaceted, simultaneously regulating the gut mucosal immune system and systemic immune system (Fig. 2d) [307][308][309][310]. It was reported that the gut microbiota of immunotherapy-sensitive patients was distinct from that of immunotherapy-resistant populations [311,312].…”
Section: Fmt Plus α-Pd-1/pd-l1mentioning
confidence: 99%
“…Although the possible immunoregulatory role of these metabolites is still under investigation, gut microbial/metabolic signatures associated with beneficial or pathogenic potential may represent novel biomarkers for monitoring intestinal and systemic inflammation during HSCT. Of note, the effect of gut microbiota in HSCT is an active research field, also in diseases other than IEI [ 90 , 91 ]. Compelling evidence shows that the gut microbiota has a role in the development of graft-versus-host disease (GvHD) both in adult and pediatric patients [ 92 , 93 ], but the exact mechanisms of this relationship need to be elucidated [ 94 ].…”
Section: Gut Microbiota–host Interactions In Human Inborn Errors Omentioning
confidence: 99%
“…Complications such as graft-versus-host disease (GVHD) remain a major cause of illness and death, limiting the broader applicability of allogeneic haematopoietic cell transplantation; a number of pre-clinical studies have shown that commensal bacteria influence the pathophysiology of GVHD [10,[17][18][19][20]. Two different strategies with targeted modulation of the GM, pre-emptive and therapeutic, have been used for the prevention and treatment of imbalances of microbial ecosystems in patients with HSCT, succinctly summarised by Yu et al [77] and many of these are currently being investigated in clinical trials.…”
Section: The Gm and Colorectal Cancermentioning
confidence: 99%